2022
DOI: 10.1038/s41586-022-04875-y
|View full text |Cite
|
Sign up to set email alerts
|

The metastatic spread of breast cancer accelerates during sleep

Abstract: The metastatic spread of cancer is achieved by the hematogenous dissemination of circulating tumor cells (CTCs). Generally, however, the temporal dynamics that dictate the generation of metastasis-competent CTCs are largely uncharacterized, often assuming that CTCs are constantly shed from growing tumors or shed as a consequence of mechanical insults 1 . Here, we observe a striking and unexpected pattern of CTC generation dynamics in both patients with breast cancer and mouse models, highlighting that the vast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
125
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(131 citation statements)
references
References 26 publications
5
125
1
Order By: Relevance
“…One previous study showed that common genes might mediate breast cancer metastasis to the brain, 21 and a later study further corroborated that the metastatic spread of breast cancer to other organs (including the brain) accelerated during sleep in both mouse and human models. 38 We further showcased that this brain metastasis of breast cancer might be associated with specific neuropathologic processes, which were captured by PSCs data driven by Alzheimer's diseaserelated neuropathology. For example, the hippocampus-entorhinal cortex PSC (C128_3, Fig.…”
Section: Discussionmentioning
confidence: 90%
“…One previous study showed that common genes might mediate breast cancer metastasis to the brain, 21 and a later study further corroborated that the metastatic spread of breast cancer to other organs (including the brain) accelerated during sleep in both mouse and human models. 38 We further showcased that this brain metastasis of breast cancer might be associated with specific neuropathologic processes, which were captured by PSCs data driven by Alzheimer's diseaserelated neuropathology. For example, the hippocampus-entorhinal cortex PSC (C128_3, Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Although current clinical practice guidelines do not yet recommend making treatment decisions based on CTCs enumeration or phenotyping for patient with metastatic breast cancer (MBC), multiple studies have confirmed that CTCs are widespread in MBC and high baseline CTC counts based on CellSearch is a well-established independent prognostic factor for worsening progression-free survival (PFS) and overall survival (OS). Moreover, dynamic changes of CTCs have a role in predicting treatment efficacy (4)(5)(6)(7)(8). The checkout rate of CTC in patients with early breast cancer (EBC) is significantly lower than that of MBC, ranging from 21.5% to 24% as reported in previous study, and≥ 1 CTC/7.5ml blood is a poor prognostic factor for disease free survival (DFS) and OS (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 98%
“…Using evolutionary ecology reasoning, Corte ´s-Herna ´ndez et al predicted that malignant cells, including CTCs, should behave differently between day and night. 3 Following the recent work of Diamantopoulou et al, 4 this is now a proven fact for CTCs, and this discovery will undoubtedly have major medical implications. Would this suggest that we have so far missed a major adaptive feature of the metastatic process?…”
mentioning
confidence: 93%
“…The main findings by Diamantopoulou et al 4 include the following: (1) a correlation between the circadian rhythm and CTC intravasation. Diamantopoulou and colleagues identified a striking and unexpected pattern of CTC-generation dynamics in both patients with breast cancer (n = 30; 21 patients were diagnosed with early breast cancer-no metastasis-and 9 were diagnosed with stage IV metastatic disease) as well as in four different mouse models.…”
mentioning
confidence: 99%